RESEARCH ON SHOT STRESS RELAXATION MODEL OF2024-T351 ALUMINUM ALLOY - GAO Pan; CHEN Ping; YIN AiJun; CHEN Cheng (Jixie qiangdu)
The residual compressive stress field introduced by shot peening can effectively improve the fatigue performance of the component, but decrease of the residual compressive stress cased by the cycle stress relaxation, thereby reducing the gain effect of residual compressive stress on fatigue performance, Therefore, in-depth study of the residual stress relaxation law will help to more accurately grasp its impact on fatigue performance.In order to systematically study the law of residual stress relaxation, the standard test piece of 2024-T351 aluminum alloy was taken as the research object, comprehensively considering the influence of stress amplitude、load conditions and the change of cold work hardening degree caused by shot peening on residual stress, a residual stress relaxation model was constructed based on theory. Through the tensile fatigue test, the relaxation model is verified based on the full life test data and the phase test data to prove the effectiveness of the model.